Photoabsorption and photocatalysis of SrSnO3 produced by a cyclic microwave radiation - Junploy P. (2014)
Rod-like hexagonal SrSn(OH)6 precursors were produced by a cyclic microwave radiation (CMR) of a template-free solution containing SnCl2·2H2O and (CH3CO2) 2Sr at the pH 12.2, adjusted by NaOH solution. The rod-like hexagonal SrSn(OH)6 precursors were calcined at 500 °C, 700 °C and 900 °C for 3 h following the thermogravimetric analysis. In the end, the perovskite orthorhombic SrSnO3 products in the shape of rods with 530 cm-1 Sn-O stretching mode, characterized by X-ray diffraction, electron microscopy and Fourier transform infrared spectroscopy, were produced. UV-visible analysis of the best crystalline rod-like SrSnO3 indicated an exponential decreasing of photonic absorption attenuated through the orthorhombic SrSnO3 solid with 3.91 eV direct energy gap, including 85% decolorization efficiency under UV light for 320 min. © 2013 Elsevier Ltd. All rights reserved.